2012
DOI: 10.4236/wja.2012.21001
|View full text |Cite
|
Sign up to set email alerts
|

Early Infant Diagnosis (EID) of HIV: An Experience at a Tertiary Care Hospital in India

Abstract: Introduction: Early infant diagnosis (EID) confers substantial benefit to HIV infected and HIV uninfected infants and to programmes providing prevention of mother to child transmission (MTCT), but has been challenging to implement in resource limited settings. Objectives: To find out the rate of perinatal transmission in infants born to HIV positive mothers, to study the effect of various predisposing factors on HIV transmission and to evaluate the utility of dried blood spot (DBS) specimen for EID of HIV. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
(13 reference statements)
2
7
0
Order By: Relevance
“…The reduced distance to access the services by mothers, early sample collection, early EID results collection and reduced loss to follow-up remain congruent with peoples’ expectations to have the children access HIV services and improve health. 39 Our findings concurred with a study in Uganda that reported an increased uptake of EID of HIV and associated this positive outcome to reduced distance, increased collection of results, and follow-up of infants at 6 weeks. 5 Our findings that the perceived benefits from early initiation of treatment, reduced morbidity, and mortality which in turn influenced their perceived acceptability for the service into VHCs corroborates with results from India.…”
Section: Discussionsupporting
confidence: 91%
“…The reduced distance to access the services by mothers, early sample collection, early EID results collection and reduced loss to follow-up remain congruent with peoples’ expectations to have the children access HIV services and improve health. 39 Our findings concurred with a study in Uganda that reported an increased uptake of EID of HIV and associated this positive outcome to reduced distance, increased collection of results, and follow-up of infants at 6 weeks. 5 Our findings that the perceived benefits from early initiation of treatment, reduced morbidity, and mortality which in turn influenced their perceived acceptability for the service into VHCs corroborates with results from India.…”
Section: Discussionsupporting
confidence: 91%
“…Five (18.5%) of exclusively breastfed babies were found to be PCR-positive [ 19 ]. In another study, it is clearly demonstrated that in children > 6 months the positivity rate was significantly higher in breast fed 42.8% (3/7) as compared to non breast fed 5% (2/40) children [ 31 ]. The more likely explanation for this is that mixed breast feeding and early initiation of complementary feeding practice exacerbate the increasing vulnerability of HIV positivity to their infants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we estimated the incidence, prevalence, and examined the role of associated factors of HIV infection, among children exposed to maternal HIV, in Belgaum district in Karnataka state in India. Few studies have tried to assess the risk of MTCT of HIV [1619] in India. They were either confined to a single facility or assessed the risk among urban dwellers only.…”
Section: Introductionmentioning
confidence: 99%